2020
DOI: 10.26434/chemrxiv.11958969.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of N,N-Di(4-bromophenyl)nitrenium Ion Under Acidic Conditions: Search for a Nitrenium Dication

Abstract: The behavior of the N,N-di(4-bromophenyl)nitrenium ion under acidic aqueous conditions was examined via laser flash photolysis experiments. A long-lived species forms and can be assigned as the cation radical or the dication. This species is unreactive towards nucleophiles and reactive towards strong electron donors, consistent with a cation radical. Mechanistic analysis indicates its formation is through a separate pathway than that of the nitrenium ion, suggestive of a triplet mechanism.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…An alternative excited state pathway for the formation of 3 is proposed. An initial version of this work was deposited on the ChemRxiv on 10 Mar 2020 …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…An alternative excited state pathway for the formation of 3 is proposed. An initial version of this work was deposited on the ChemRxiv on 10 Mar 2020 …”
Section: Introductionsupporting
confidence: 92%
“…An initial version of this work was deposited on the ChemRxiv on 10 Mar 2020. 16 ■ RESULTS AND DISCUSSION LFP Generation of Nitrenium Ion 2 at Varying pHs. Figure 1 (top) shows the transient absorption spectrum resulting from pulsed laser (355 nm, 50 mJ/pulse, 7 ns) photolysis of pyridinium ion 1 in aqueous solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies of other diarylnitrenium ions have shown some level of radical cation formation under certain conditions [48]. These have been attributed to reactions of nitrenium ion triplet states and/or branching from the initially formed pyridinium excited states.…”
Section: Resultsmentioning
confidence: 98%